Efektivitas Penggunaan Bahan Ajar Lembar Kerja Siswa (LKS) dalam Metode Diskusi untuk Meningkatkan Minat Belajar Siswa - Rima Dina Mawar Ningrum; Asep Hidayat; Sungging Handoko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2012)
This research was conducted to determine the differences in student learning interest between the experimental class and the control class after the learning process was carried out. This type of research is experimental research, with a Quasi Experiment control group design, which is quantitative in nature. With the population of this study were high school students BPI 2 Bandung class X, while the sample of this study was class X-2 as a control class totaling 33 students and X-3 as an experimental class amounting to 32 students. This research was carried out at SMA BPI 2 Bandung. From the results of data analysis in this study, the use of LKS teaching materials in the Discussion Method is effectively used to increase student learning interest. Thus the use of LKS teaching materials in the discussion method has a positive influence on student learning interest and is effectively used to increase student learning interest.